Geomorphology of marine and transitional terraces and raised shorelines between Punta Paulo and Porvenir, Tierra del Fuego, Straits of Magellan – Chile. Issue 2 (30th November 2017) - DeMuro, Sandro; Brambati, Antonio; Tecchiato, Sira; Porta, Marco; Ibba, Angelo
ABSTRACT: This paper presents a coastal geomorphology map of some of the Chilean region of the Straits of Magellan, and is based on a combined geomorphological and sedimentological approach applicable to a larger section of the coast. The mapped area is located in Tierra del Fuego between the Segunda Angostura of the Straits of Magellan and Bahía Inútil. A detailed geomorphological map was compiled at a scale of 1:50, 000, describing a sequence of 4 marine and transitional (glacio-lacustrine to marine) terrace orders and raised marine shorelines found between 0 and + 20 m. These features are mainly linked to glacio-eustasy and secondarily to Holocene neo-tectonics. This research derives from the interpretation of aerial photographs and remote sensing imagery along with geomorphological-stratigraphic field surveys and geochemical data. The Main Map illustrates an area with dominant palaeo-glacial and glacio-lacustrine morphology with extensive lacustrine deposits and well-developed lake systems characterising the Porvenir region.